Performance and conceptual structure of climate-smart agriculture research: a bibliometric analysis (2010–2023) - Manyike, Jabulile Zamokuhle; Ningi, Thulani; Mokhaukhau, Jenny Potsiso; Maka, Loquitur (Frontiers in Sustainable Food Systems, 2025)
Climate-smart agriculture (CSA) plays a crucial role in addressing the global impacts of climate change by integrating adaptation and mitigation strategies into agricultural practices. Despite its growing importance, a comprehensive analysis of the CSA research landscape is essential to understanding its development and key trends, informing future research and policy formulation. This study investigates the evolution and current state of CSA research from 2010 to 2023, with a focus on its conceptual structure and thematic development. Data sourced from the Scopus database were analysed using bibliometric techniques. The findings reveal an increasing volume of academic publications, indicating heightened global interest in CSA. The study uncovers strong interconnections among CSA practices, economic implications, sustainability, policy development, practical implementation, and regional adaptation. Notably, there has been a shift from foundational concepts to practical applications, reflecting the field’s maturation in response to challenges in agricultural sustainability and climate change mitigation. However, significant gaps persist in exploring CSA’s socio-economic dimensions and integrating diverse knowledge systems. Future research should prioritize the socio-economic impacts of CSA practices on household income and food security, ensuring equitable implementation across regions. Additionally, targeted studies on technology adoption and greenhouse gas emissions mitigation are necessary. Emphasis should be placed on developing context-specific and culturally relevant strategies, analysing the global political economy’s influence on CSA, and incorporating nuanced critiques of CSA’s effectiveness. This study provides a valuable framework for future research, aiming to enhance the effectiveness and sustainability of CSA in addressing global climate challenges.